1994
DOI: 10.1002/1097-0142(19940315)73:6<1552::aid-cncr2820730605>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase-producing sialyl Lea and sialyl Lex carbohydrate antigen in benign and malignant gastrointestinal mucosa

Abstract: Background. Sialyl Lea antigen and sialyl Lex antigen are cancer‐associated carbohydrate antigens. Previous immunohistologic and immunochemical studies have shown that these antigens are preferentially expressed in gastric cancer and colonic cancer and that they possibly are related to the metastatic potential of the cancer cells. The biosynthesis of these antigens is completed by fucosyltransferases, but it has not been reported how fucosyltransferases control the expression of these carbohydrate antigens con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…This is demonstrated, for example, by the occurrence of abnormal synthesis of mucus glycoproteins [Lewis blood groups, Ca 19-9, sialyl Le(x)], and unexpected expression of abnormal gene products (K-ras) in gastritic stomach or intestinal metaplasia without any evidence of coexist, overt precancerous lesions, such as dysplasia or adenoma. [5][6][7][8][9][10][11] It seems plausible that an array of various genotoxic affections are triggered by the H. pylori gastritis, and that the resulting gene errors may play a role as effector mechanisms modulating the further course and outcomes of the H. pylori acquisition. Correspondingly, it is possible that even atrophic gastritis may result from unknown mutations in epithelial cell genes and may, thereby, stem from an imbalance between abnormal proliferation and death (apoptosis) of the epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…This is demonstrated, for example, by the occurrence of abnormal synthesis of mucus glycoproteins [Lewis blood groups, Ca 19-9, sialyl Le(x)], and unexpected expression of abnormal gene products (K-ras) in gastritic stomach or intestinal metaplasia without any evidence of coexist, overt precancerous lesions, such as dysplasia or adenoma. [5][6][7][8][9][10][11] It seems plausible that an array of various genotoxic affections are triggered by the H. pylori gastritis, and that the resulting gene errors may play a role as effector mechanisms modulating the further course and outcomes of the H. pylori acquisition. Correspondingly, it is possible that even atrophic gastritis may result from unknown mutations in epithelial cell genes and may, thereby, stem from an imbalance between abnormal proliferation and death (apoptosis) of the epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…The reaction mixture contained 25 mM HEPES (pH 7.2), 20 mM MnCl 2 , 0.45% Triton CF54, 0.04 mM oligosaccharide-aminopyridine, 2 mM GDP-fucose, 5 mM CDP-choline, and 200 g of protein in a volume of 0.05 ml (27).…”
Section: Methodsmentioning
confidence: 99%
“…15-18 Our preliminary studies indicated that sLeX, a glycan which binds with strong affinity to the E-selectin, facilitates HNSCC binding to EC under conditions of flow. 19,20 Expression of sLeX has been observed in several human malignancies, including HNSCC, and circulating levels of sLeX positive tumor cells were reported to be predictive for metastasis in GI carcinomas.…”
Section: Introductionmentioning
confidence: 93%